Nile tilapia post-larvae production in a recirculating aquaculture system with rectangular tanks and different water inlet designs - Souza, Michael Blank de; Silva, Tuanny Trindade da; Leal, Heloise Nantes Romero; Alves Neto, Ademar; Neu, Dacley Hertes; Hilbig, Cleonice Cristina; Lewandowski, Vanessa (Revista de Ciências Agroveterinárias, 2021)
The aim of the present study was to evaluate the effect of the water inlet design in rectangular tanks, on the water quality and productive performance of Nile tilapia post-larvae. 720 animals weighing 0.02 g and 12.52 mm in length were distributed in 12 rectangular tanks, with a length/width ratio of 1.20 and a water inlet flow of 3.2 times the useful volume of the tanks. The treatments consisted of three water inlet designs: upper, single vertical submerged, and double vertical submerged, distributed in four replicates each. Productive performance (weight and final length, specific growth rate, condition factor and survival) and water quality (pH, dissolved oxygen, temperature, dissolved solids and electrical conductivity) parameter were evaluated. Dissolved oxygen was evaluated at the four ends and center of each tank to check for dead zones. In addition, the suspended solids concentration was evaluated 30 minutes after feeding at 21 days of study. The water inlet design did not influence the productive performance and the general parameter of water quality (p>0.05). There was no difference in the concentration of dissolved oxygen within the tank for each treatment, which indicates that there was no formation of dead zones (p>0.05). There was a difference in the concentration of dissolved oxygen in the extremities and the center of the tanks due to the treatments, where the lowest values were verifies for the tanks with submerged vertical water inlet (p<0.05). The tanks with submerged vertical double inlets showed a lower concentration of suspended solids, compared to the other treatments (p<0.05). Thus, the use of a single vertical submerged inlet is not indicated and there was no negative influence on production performance and water quality, it is possible to produce Nile tilapia post-larvae with upper water inlet.